2000
DOI: 10.1097/00005768-200007000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue after submaximal intensive stretch-shortening cycle exercise

Abstract: It was concluded that after submaximal stretch-shortening exercise, the low-frequency fatigue occurred, very likely caused by lower Ca2+ release per single action potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
2
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 20 publications
7
40
2
3
Order By: Relevance
“…Moreover, our between session ratio reliability was excellent (ICC > 0.92). Therefore, we believe that the D/S ratio was highly sensitive to LFF as supported by others (Strojnik and Komi, 2000;Tubman et al, 1997).…”
Section: Comparisons With Previous Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, our between session ratio reliability was excellent (ICC > 0.92). Therefore, we believe that the D/S ratio was highly sensitive to LFF as supported by others (Strojnik and Komi, 2000;Tubman et al, 1997).…”
Section: Comparisons With Previous Studiessupporting
confidence: 75%
“…We used the D/S ratio to quantify LFF even though others have used higher frequency trains (e.g., Skurvydas et al, 2003;Strojnik and Komi, 2000;Ratkevicius et al, 1998). Single and double pulses were employed in the present study rather than trains because they induce less co-contraction because they are more comfortable, and, therefore, allow a greater intensity of stimulation.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…More specifically, fatiguing SSC exercise generally leads to an immediate reduction in maximal voluntary contraction (MVC) force and electromyography (EMG) (Avela et al 1999;Skurvydas et al 2000;Kuitunen et al 2002;Millet et al 2003) as well as to reduced reflex sensitivity (Nicol et al 1996;Avela et al 1999). On the other hand, a post exercise increase in maximal voluntary EMG (Strojnik and Komi 2000) and stretch reflex response (Hortoba´gyi et al 1991) have also been reported after short-term SSC exercise (herein <10 min), despite the reduction in the MVC force. These results indicate that the factors underlying the acute post exercise MVC force deficit may vary depending, among others, on the duration and intensity of the SSC exercise.…”
Section: Introductionmentioning
confidence: 92%
“…It does not come from an increase in mechanical work production or from increase in muscular activation. There seems to be no failure of the excitation-contraction coupling, which has been reported for stretch-shortening cycle exercises of short (Strojnik and Komi 2000) and long duration (Nicol et al 1991). Therefore, as there was no increase in EMG as a function of running time, it seems unlikely that increase in muscle fibre recruitment occurs in the present type of running protocol.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, muscle fatigue would have been more important in these previous studies. Thus, EMG levels would have increased to counteract the failure of the excitation-contraction coupling (Gollhofer et al 1987;Strojnik and Komi 2000) that occurred with muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%